Sistem Pendukung Keputusan Pemilihan Lokasi Pre-Wedding di Kota Medan dengan Menggunakan Metode VIKOR dan BORDA - Ade Syahputra (STMIK Budi Darma, 2020)
Decision Support System for the selection of pre-wedding locations using the Vikor and Borda methods. A tool has been made to select the pre-wedding location in the city of Medan. The criteria used in the decision support system for pre-wedding location selection are: access to the location, costs, location conditions and location situation. Knowing the process of selecting the best pre-wedding location that is still experiencing obstacles in the process of decision-making results for brides who want to do a pre-wedding photo session. Pre-wedding venue selection is very important because it determines the good results of the pre-wedding photo. Very many places that are very suitable for pre-wedding photo sessions for example in the city of medan. Decision Support Systems can come in forms, ranging from simple forms of data management to complex application forms and can also be used to accelerate and improve the quality of decision making processes in an organization